Rigid-flexible Coupling Modeling and Fault Characteristic Simulation Research of Planetary Transmission System - Zihan Wang; Fuzhou Feng; Hua Cong; Jie Wang (Jixie chuandong)
For a certain type of tank planetary gearbox K3 planet row， in order to research the influence of the fault gear on the dynamic characteristic of planetary transmission system， by using Solid works， Adams and Ansys software， a rigid-flexible coupling dynamic model is established， as well as conducting joint simulation analysis. It is verified that the rigid-flexible coupling model has more obvious vibration response in the time and frequency domain than the pure rigid body model. By drawing the stress change curve of the dangerous node， the equivalent stress distribution cloud graph at the time of the maximum stress is obtained. The cause of gear spalling fault is clarified and fault operation is simulated. By comparing and analyzing the simulation signals of contact force and acceleration under normal conditions， the time and frequency response characteristics of gear spalling faults are obtained. The simulation results can provide basic basis and theoretical support for the research on the fault mechanism and fault diagnosis technology of the planetary gearbox.